Study of ignition, combustion, and production of harmful substances upon burning solid organic fuel at a test bench with a vortex chamber; Thermal Engineering; Vol. 63, iss. 1 - Burdukov A. P.; Chernetskiy M. Yu.; Dekterev A. A.; Anufriev I. S.; Strizhak P. A. Pavel Alexandrovich; Greben’kov P. Yu. (2016, 2016)
Title screen